Tanggung Jawab Pengemudi Ambulan Karena Kelalaiannya Mengakibatkan Kecelakaan Lalu Lintas Berdasarkan Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan - Maknun, Luil (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
As a result of the fact that Indonesian people generally own private vehicles, many vehicle dealers, both cars and motorcycles, offer low selling prices to the public, which indirectly causes the public's desire to own vehicles. By buying this car, you can meet all your needs for fast, easy, and personally accessible transportation. Normative law research used. Governments and police should regularly socialize traffic laws and traffic regulations in places like schools and in media such as newspapers, television, and radio. In order to ensure that the handling of traffic violations is smooth and running as expected, the Traffic Police is expected to improve its performance and pay more attention to the quality and quantity of staff.